2020
DOI: 10.1002/bjs.11510
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence or X-ray cholangiography in elective laparoscopic cholecystectomy: a randomized clinical trial

Abstract: Background: Safe laparoscopic cholecystectomy may necessitate biliary imaging, and non-invasive fluorescence cholangiography may have advantages over contrast X-ray cholangiography. This trial compared fluorescence and X-ray cholangiography for visualization of the critical junction between the cystic, common hepatic and common bile ducts. Methods: This non-inferiority blinded RCT included patients who had either intraoperative fluorescence cholangiography using 0⋅05 mg/kg indocyanine green or X-ray cholangiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
0
32
1
Order By: Relevance
“…We appreciate and thank Mroczkowski and Dziki for their valuable comments and interest in our recent trial. We agree completely that cholangiography (X‐ray or fluorescent) cannot replace a careful surgical technique.…”
mentioning
confidence: 54%
“…We appreciate and thank Mroczkowski and Dziki for their valuable comments and interest in our recent trial. We agree completely that cholangiography (X‐ray or fluorescent) cannot replace a careful surgical technique.…”
mentioning
confidence: 54%
“…22 Hence, ICG has very high safety. 3,25 Lehrskov et al 26 recently conducted a noninferiority blinded randomized controlled trial of patients who underwent either intraoperative fluorescence cholangiography (n ¼ 60) or X-ray cholangiography (n ¼ 60) during elective LC. The authors concluded that fluorescence cholangiography was noninferior to X-ray cholangiography in visualizing the critical junction during LC.…”
Section: Discussionmentioning
confidence: 99%
“…NIR-ICG has been shown to be useful in identifying biliary structures in LC, however, its role in bile duct detection and prevention has not been established. The results reported from prior studies have mostly concluded that NIR-ICG improves visualisation of biliary structures; however, these studies included a relatively small sample size, ranging between 23 and 120 patients (36,38). Several groups(39-41) have found NIR-ICG to be feasible, although it has not been validated against IOC, which is the standard for visualisation of the critical junction.…”
Section: Why Is It Important To Do This Review?mentioning
confidence: 99%